Social, Cognitive and Traditional Motives in Christmas Market Tourism: A Case Study from Poland - MŁYNKOWIAK-STAWARZ, Anna; BĘBEN, Robert (Journal of Environmental Management and Tourism, 2024)
This study offers a novel and significant contribution to the understanding of cultural tourism by exploring visitor motivations at one of Poland's largest Christmas markets, situated in Gdańsk. While Christmas markets are deeply rooted in European tradition, research on their appeal in the context of contemporary consumer behaviour, especially in the face of globalisation and secularisation, remains limited. By examining a diverse range of motives - spanning from social gatherings and shopping to tradition and inspiration - this research provides a fresh perspective on how Christmas markets can cater to both traditional and evolving interests. The study’s insights highlight how event-driven tourism can effectively support regional visitation beyond peak tourist seasons, offering a model that could be applied to other locations seeking to expand their tourism appeal throughout the year. Furthermore, the findings emphasise the strategic importance of culturally significant events in strengthening the tourism economy and community engagement within the Baltic region and beyond.